Non-woven material with high water absorbability for facial mask and preparation method of non-woven material

Through the preparation of microcrosslinked gel particles and nano microspheres, the problems of uneven water absorption and molecular chain breakage in the water absorption process of nonwoven materials for facial masks are solved, and high water absorption and good water molecule release effect are achieved, improving the The moisturizing properties and comfort of the mask.

CN119221203AActive Publication Date: 2024-12-31WEIFANG GUANGLI NEW MATERIAL TECH CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411773692.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2024-12-31
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The existing nonwoven materials for facial masks have problems such as uneven water absorption, uneven surface and internal reaction, breaking of the molecular chain of sodium alginate, causing sticky feeling and poor moisturizing effect during the water absorption process.

Method used

The preparation method of micro-crosslinked gel particles and nano-microspheres is adopted, and the hydrogen bonding of carboxymethyl chitosan and sodium alginate is connected to the catalysis of glycerol and calcium chloride to form an ester-based crosslinking point, nano-micro The ball fixes calcium ions through surface treatment, controls cross-linking density and speed, and improves water absorption and water molecule release ability.

Benefits of technology

It achieves high water absorption and has a small dimensional change rate after water absorption, without any greasy feeling, water molecules are easily released, good water replenishment effect, stable fiber structure, and unaffected effective ingredients transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221203A_ABST
    Figure CN119221203A_ABST
Patent Text Reader

Abstract

The invention discloses a non-woven material with high water absorbability for a facial mask and a preparation method of the non-woven material, and belongs to the technical field of non-woven materials, the preparation method comprises the following steps: preparing micro-crosslinked gel particles, preparing nano microspheres, preparing a first fiber web, preparing a second fiber web, spunlacing, dipping for the first time, dipping for the second time and post-processing; the preparation of the micro-crosslinking gel particles comprises the following steps: preparing a mixed solution, and carrying out micro-crosslinking; the method for preparing the nano microspheres comprises the following steps: silanization and grafting; the prepared non-woven material for the mask has high water absorption performance, the size change rate after water absorption is small, obvious sticky feeling cannot be generated in the using process, the formula of a mask material body cannot be affected, collapse of a fiber structure cannot be caused, transmission of effective components cannot be affected, water molecules are easily released after water absorption, and the non-woven material for the mask has a good water absorption effect. The water replenishing effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonwoven materials, and in particular to a nonwoven material for a facial mask with high water absorption and a preparation method thereof. Background Art

[0002] Nonwoven materials are fabrics that do not require spinning and weaving. During preparation, textile short fibers or filaments are oriented or randomly arranged to form a fiber mesh structure, and then reinforced by mechanical, thermal bonding or chemical methods. Nonwoven materials have excellent air permeability, hygroscopicity and softness, and are widely used in medical, clothing, agriculture and industrial fields. In addition, they are also widely used in various facial mask products, such as moisturizing masks, whitening masks and firming masks. When used in facial mask products, nonwoven materials are mainly used as carriers of facial masks. Due to the excellent hygroscopicity of nonwoven materials, they can absorb essence and promote the even distribution of essence on the skin surface, thereby playing a role in hydrating and moisturizing, and helping the skin absorb nutrients. Moreover, due to the excellent air permeability and softness of nonwoven materials, they can not only promote blood circulation in the deep layer of the skin and accelerate skin metabolism, but also have a high degree of fit with the skin.

[0003] In order to ensure excellent air permeability, moisture absorption and softness, nonwoven materials for facial masks are mainly made of natural fibers such as wood pulp fiber, corn fiber, silk, etc. However, nonwoven materials for facial masks made of natural fibers have poor water absorption, which affects the absorption of essence by the mask and further affects the moisturizing effect of the mask.

[0004] Gel is an elastic semisolid, which is a three-dimensional network structure formed by the interconnection of colloidal particles or polymers in a sol or solution under certain conditions. It can capture solvents and restrict the flow of solvents. It is mainly divided into oil gel and hydrogel. Among them, hydrogel can form a three-dimensional network structure through hydrophilic gelling agents, thereby fixing the water phase. Polysaccharides are naturally occurring biopolymers in nature, which are easy to obtain and low in cost. They are excellent hydrogels. There are a large number of hydrophilic groups such as hydroxyl and amino groups in the molecular structure of polysaccharides, which can interact with a large number of water molecules to form hydrates. Polysaccharides are made into non-woven fabrics to obtain non-woven materials with excellent water absorption.

[0005] As a polysaccharide with a linear structure, sodium alginate has excellent biocompatibility and biodegradability, and is non-toxic and non-irritating. The molecules of sodium alginate contain a large number of hydroxyl groups, carboxyl groups and sodium carboxyl groups. The hydroxyl groups and carboxyl groups in sodium alginate can form hydrogen bonds or other adsorption forces with water molecules, thereby adsorbing water molecules. Since both hydroxyl groups and carboxyl groups belong to polar groups, they can also interact with unadsorbed water molecules, thereby forming a multi-layer water molecule layer on the surface of sodium alginate, and sodium carboxyl groups can ionize sodium ions in water. Sodium ions are metal cations with strong hydration ability, which can adsorb a large number of water molecules, thereby ensuring that sodium alginate has excellent water absorption. Therefore, using sodium alginate as a raw material, a nonwoven material for a facial mask with excellent water absorption can be prepared. In addition, the sodium alginate in the nonwoven material for a facial mask prepared with sodium alginate as a raw material can also play the role of moisturizing, promoting skin healing, antibacterial and anti-inflammatory.

[0006] When preparing non-woven materials for facial masks using sodium alginate as raw material, the most commonly used preparation method is to make calcium alginate fibers into spunlace non-woven materials through a spunlace reinforcement method, and then use a sodium salt solution for impregnation. Calcium alginate fibers have excellent gelling properties. After contacting with sodium ions in the sodium salt solution, ion exchange will occur, and calcium alginate will be converted into sodium alginate, releasing calcium ions. The G units in the sodium alginate are combined through synergistic action to form a diamond-shaped hydrophilic space. Some of the released calcium ions occupy the above-mentioned diamond-shaped hydrophilic space and are cross-linked with multiple atoms in the G unit to form an "egg box" structure, thereby increasing the binding force between the sodium alginate molecular chains and promoting the formation of a three-dimensional network structure, namely, a hydrogel, which is then dried to obtain the non-woven material for facial masks. Chinese patent CN110787067A discloses a deep hydrating facial mask without preservatives and thickeners and a preparation method thereof. The facial mask is a spunlace nonwoven material with a double-layer structure, one layer of which is composed of calcium alginate fibers and the other layer is composed of other fibers. When preparing the facial mask, the "two combs and one paving" process is adopted, and calcium alginate fibers of specific specifications are selected to be compounded with other fibers, and the nonwoven material is made by a spunlace reinforcement method, and then the spunlace nonwoven material is sequentially impregnated with a sodium salt solution and a polyol solution, and then cut, cut, folded, bagged, irradiated and sealed to obtain a facial mask after drying. The facial mask prepared by the invention forms a gel that can be absorbed by the skin after absorbing water, and the application time can reach more than 40 minutes.

[0007] However, the above method has the following shortcomings: first, the sodium salts in the sodium salt solution used mainly include sodium chloride, sodium carbonate, sodium bicarbonate, disodium ethylenediaminetetraacetic acid, and sodium citrate. However, when sodium chloride, sodium carbonate, sodium bicarbonate, disodium ethylenediaminetetraacetic acid, and sodium citrate are subjected to ion exchange with calcium alginate, there is a problem of too fast ion exchange rate, which leads to preferential ion exchange and cross-linking on the surface of the calcium alginate fiber, thereby forming a dense cross-linked film on the surface of the calcium alginate fiber, affecting the ion exchange inside the seaweed fiber, resulting in uneven surface and internal reactions, affecting the water absorption of the prepared non-woven material for facial mask, and also leading to inconsistent surface and internal water absorption during water absorption, and a large dimensional change rate after water absorption; second, during the ion exchange process, the generated sodium alginate will absorb water and swell, and the molecular chain of sodium alginate is unstable. During the water absorption and swelling process, the molecular chain of sodium alginate will partially break and break into small molecule sodium alginate, which is easy to separate from the three-dimensional network structure. Separation causes the formula of the mask material to change, affecting the use effect; and during use, small molecule sodium alginate dissolves in water to form an aqueous solution. As the water evaporates, it will adhere to the surface of the non-woven material, causing the collapse of the fiber structure and forming a dense film, which affects the transfer of effective ingredients and also causes the surface to be sticky. After use, there is an obvious sticky feeling, which is specifically manifested in that after the prepared non-woven material for the mask is soaked in water for several hours, the small molecule sodium alginate leaves the surface of the non-woven material and dissolves in the water. The water contains small molecule sodium alginate, and the stickiness of the prepared non-woven material for the mask will be weakened after use; thirdly, when the prepared non-woven material for the mask absorbs water molecules, the hydrogen bond between the polar group and the water molecules is the main effect. Since hydrogen bond is a strong intermolecular force, the adsorbed water molecules and effective ingredients are not easy to separate from the non-woven material for the mask, resulting in the prepared non-woven material for the mask having an excellent water-locking effect, but failing to replenish water and effective ingredients. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a non-woven material for facial mask with high water absorption and a preparation method thereof. The prepared non-woven material for facial mask not only has high water absorption, but also has a small dimensional change rate after absorbing water, and does not produce obvious sticky feeling during use, and will not affect the formula of the mask material body, nor cause the collapse of the fiber structure to affect the transfer of effective ingredients. Moreover, after absorbing water, water molecules are easily released, and the moisturizing effect is good.

[0009] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a nonwoven material for a facial mask with high water absorption, comprising the following steps: preparing micro-crosslinked gel particles, preparing nano-microspheres, preparing a first fiber web, preparing a second fiber web, hydroentangling, primary dipping, secondary dipping, and post-treatment; The method for preparing micro-crosslinked gel particles comprises the following steps: preparing a mixed solution, micro-crosslinking; The mixed solution is prepared by adding carboxymethyl chitosan and the first portion of deionized water into a reactor, controlling the temperature of the reactor to 40-50° C., controlling the stirring speed to 200-400 rpm, and stirring for 20-30 minutes to obtain a carboxymethyl chitosan aqueous solution; adding sodium alginate and the second portion of deionized water into a reactor, controlling the temperature of the reactor to 40-50° C., controlling the stirring speed to 200-400 rpm, and stirring for 20-30 minutes to obtain a sodium alginate aqueous solution; mixing the carboxymethyl chitosan aqueous solution, the sodium alginate aqueous solution, and glycerol, adding the mixture to an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to 25-30 kHz, and ultrasonically oscillating at room temperature for 30-40 minutes to obtain a mixed solution; In the prepared mixed solution, the dosage ratio of carboxymethyl chitosan, the first portion of deionized water, sodium alginate, the second portion of deionized water, and glycerol is 10-15 g: 1000-1100 mL: 14-16 g: 1000-1100 mL: 0.7-0.8 mL; The carboxymethyl chitosan has a carboxymethyl substitution degree of 0.9, a deacetylation degree of 90%, and a viscosity average molecular weight of 240 kDa; The micro-crosslinking comprises adding the mixed solution and ethyl acetate into a reactor, controlling the stirring speed to 500-600 rpm, stirring at room temperature for 3-3.5 hours, removing the ethyl acetate by reduced pressure distillation, and then adding calcium chloride and citric acid into a reactor, controlling the temperature of the reactor to 90-95° C., controlling the stirring speed to 200-400 rpm, stirring for 50-60 minutes, transferring to a dialysis bag with a molecular weight cutoff of 8000 Da, dialyzing with deionized water for 40-50 hours, replacing the deionized water every 6-8 hours, and then transferring to a vacuum freeze dryer, controlling the temperature of the vacuum freeze dryer to -40° C. to -30° C., controlling the vacuum degree to 80-100 Pa, and vacuum freeze drying for 25-30 hours to obtain micro-crosslinked gel particles; The ratio of carboxymethyl chitosan in the prepared mixed solution to ethyl acetate, calcium chloride and citric acid in the micro-crosslinking is 10-15 g: 9000-9200 mL: 0.2-0.3 g: 0.5-0.6 g; The preparation of nano-microspheres is composed of the following steps: silanization and grafting; The silanization comprises mixing fumed silica, deionized water and anhydrous ethanol and adding the mixture to an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to 25-30 kHz, ultrasonically oscillating at room temperature for 30-40 minutes, transferring the mixture to a reactor with a reflux device, controlling the temperature in the reactor to 45-55° C., controlling the stirring speed to 200-400 rpm, adding vinyl trimethoxysilane and 3-aminopropyl trimethoxysilane, stirring and refluxing for 10-20 minutes, dropping dilute hydrochloric acid to adjust the pH to 4-4.5, stirring and refluxing for 5-6 hours, transferring the mixture to a centrifuge, controlling the centrifugal speed of the centrifuge to 11000-12000 rpm, centrifuging for 18-20 minutes, washing the precipitate with anhydrous ethanol and vacuum drying the mixture to obtain silanized fumed silica; In the silanization, the usage ratio of fumed silica, deionized water, anhydrous ethanol, vinyl trimethoxysilane and 3-aminopropyl trimethoxysilane is 37-40 g: 400-500 mL: 2400-2600 mL: 5-5.5 g: 30-32 g; The particle size of the fumed silica is 40 nm; The mass concentration of the dilute hydrochloric acid is 10%; The grafting comprises adding silanized fumed silica, 4-vinylpyridine, styrene and acetone into a reactor, continuously introducing nitrogen into the reactor at a rate of 900-1000 mL / min, controlling the stirring speed of the reactor to 200-400 rpm, stirring at room temperature for 25-35 min, controlling the temperature in the reactor to 60-70° C., adding azobisisobutyronitrile, stirring for 5-6 h, transferring to a centrifuge, controlling the centrifugal speed of the centrifuge to 11000-12000 rpm, centrifuging for 18-20 min, washing the precipitate with acetone and vacuum drying to obtain nano-microspheres; The amount ratio of the fumed silica in the silanization to the 4-vinylpyridine, styrene, acetone, and azobisisobutyronitrile in the grafting is 37-40 g: 48-50 mL: 45-50 mL: 7000-7500 mL: 3.2-3.5 g; The first fiber web is prepared by opening, combing and laying the calcium alginate fibers to obtain the first fiber web; The diameter of the calcium alginate fiber is 9-20 μm; The first fiber web has a grammage of 10-15 g / m 2 ; The second fiber web is prepared by opening, combing and laying the second fibers to obtain the second fiber web; The second fiber is one of tencel fiber, viscose fiber and cotton fiber; The diameter of the second fiber is 9-20 μm; The second fiber web has a grammage of 20-40 g / m 2 ; The hydroentanglement is to stack the first fiber web and the second fiber web, perform hydroentanglement reinforcement and then dry to obtain a hydroentangled nonwoven material; The primary impregnation comprises winding the spunlace nonwoven material on a warp beam, and then adding the spunlace nonwoven material into a warp beam cylinder, adding a primary impregnation liquid into the warp beam cylinder, controlling the temperature in the warp beam cylinder to be 40-50° C., and promoting the primary impregnation liquid to circulate from inside to outside and from outside to inside by a circulation pump, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 4-5 cycles, and a total cycle time of 20-25 minutes. After the cycle is completed, the primary impregnation liquid in the warp beam cylinder is discharged to obtain a nonwoven material after the primary impregnation; The preparation method of the primary impregnation liquid is as follows: adding micro-crosslinked gel particles and deionized water into a reaction kettle, controlling the stirring speed to 200-300 rpm, stirring for 15-20 minutes, and obtaining the primary impregnation liquid; In the preparation of the primary impregnation solution, the ratio of micro-crosslinked gel particles to deionized water is 11-12 g: 2700-3000 mL; The usage ratio of the spunlace nonwoven material to the primary impregnation liquid is 100-120 g: 2700-3000 mL; The secondary impregnation maintains the temperature in the warp axis cylinder during the primary impregnation at 40-50°C, adds secondary impregnation liquid to the warp axis cylinder, and promotes the secondary impregnation liquid to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 4-5 cycles, and a total cycle time of 20-25 minutes. After the cycle, the secondary impregnation liquid in the warp axis cylinder is discharged, a primary cleaning liquid is added, and a primary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 2-3 cycles, and a total cycle time of 10-15 minutes. After the cycle, the primary cleaning liquid in the warp axis cylinder is discharged, and a secondary cleaning liquid is added, and the secondary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump, so as to From inside to outside once, and then from outside to inside once as one cycle, a total of 2-3 cycles, the total cycle time is 10-15min, after the cycle is completed, the secondary cleaning liquid in the warp axis cylinder is discharged, and the tertiary cleaning liquid is added, and the tertiary cleaning liquid is promoted by a circulation pump to circulate from inside to outside and from outside to inside, and from inside to outside once, and then from outside to inside once as one cycle, a total of 2-3 cycles, and the total cycle time is 10-15min, after the cycle is completed, the tertiary cleaning liquid in the warp axis cylinder is discharged, and the quaternary cleaning liquid is added, and the quaternary cleaning liquid is promoted by a circulation pump to circulate from inside to outside and from outside to inside, and from inside to outside once, and then from outside to inside once as one cycle, a total of 2-3 cycles, and the total cycle time is 10-15min, and after the cycle is completed, it is rolled and dried to obtain a non-woven material after secondary impregnation; The preparation method of the secondary impregnation liquid is as follows: sodium salt and ethanol aqueous solution are added into a reaction kettle, the stirring speed is controlled to 200-300 rpm, the stirring is performed for 15-20 minutes, and then the mixture is mixed with nano-microspheres and added into an ultrasonic oscillator, the frequency of the ultrasonic oscillator is controlled to 25-30 kHz, and the mixture is ultrasonically oscillated for 30-40 minutes at room temperature to obtain the secondary impregnation liquid; In the preparation of the secondary impregnation solution, the dosage ratio of sodium salt, ethanol aqueous solution and nano-microspheres is 55-60 g: 2700-3000 mL: 13-15 g; The sodium salt is one of sodium chloride, sodium carbonate, sodium bicarbonate, disodium ethylenediaminetetraacetate, and sodium citrate; In the preparation of the secondary impregnation solution, the volume fraction of ethanol in the ethanol aqueous solution is 45-85%; The amount ratio of the spunlace nonwoven material in the first dipping to the secondary dipping liquid in the second dipping is 100-120 g: 2700-3000 mL; The primary cleaning solution is an ethanol aqueous solution with a volume fraction of 45%; The amount ratio of the spunlace nonwoven material in the first immersion to the first cleaning liquid in the second immersion is 100-120 g: 2700-3000 mL; The secondary cleaning solution is an ethanol aqueous solution with a volume fraction of 55%; The amount ratio of the spunlace nonwoven material in the first immersion to the secondary cleaning liquid in the second immersion is 100-120 g: 2700-3000 mL; The three cleaning solutions are 75% ethanol water solution by volume; The amount ratio of the spunlace nonwoven material in the first immersion to the tertiary cleaning solution in the second immersion is 100-120 g: 2700-3000 mL; The four cleaning solutions are 95% ethanol aqueous solution by volume; The amount ratio of the spunlace nonwoven material in the first immersion to the fourth cleaning liquid in the second immersion is 100-120 g: 2700-3000 mL; The post-treatment is to cut, bag, sterilize and package the nonwoven material after the second impregnation to obtain the nonwoven material for facial mask.

[0010] A nonwoven material for facial mask with high water absorption prepared by the aforementioned preparation method.

[0011] Compared with the prior art, the present invention has the following beneficial effects: (1) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention uses micro-crosslinked gel particles in the first impregnation and nano-microspheres in the second impregnation. When preparing the micro-crosslinked gel particles, carboxymethyl chitosan and sodium alginate are first dissolved separately, mixed with glycerol, and then dispersed in ethyl acetate to form a nano-hydrogel. The carboxymethyl chitosan and sodium alginate in the nano-hydrogel are mainly connected by intermolecular forces such as hydrogen bonds. After the ethyl acetate is removed by vacuum distillation, calcium chloride and citric acid are added. The citric acid catalyzes the reaction between the carboxyl group in the carboxymethyl chitosan in the nano-hydrogel and the hydroxyl group in the sodium alginate to generate an ester group. The glycerol acts as a crosslinking agent. Through the reaction of hydroxyl groups with carboxyl groups in carboxymethyl chitosan, cross-linking is carried out in the nano hydrogel. Calcium chloride not only acts as a catalyst but also can serve as a cross-linking point. By controlling the amount of glycerol, calcium chloride and citric acid added, the degree of cross-linking is controlled to achieve micro-cross-linking, and nano-scale micro-cross-linked gel particles containing ester groups are obtained. In a single impregnation, a non-woven material is impregnated with a primary impregnation liquid containing micro-cross-linked gel particles. The micro-cross-linked gel particles are adsorbed on the surface of the non-woven material through intermolecular forces such as hydrogen bonds. The sodium ions in the micro-cross-linked gel particles are exchanged with the calcium ions in the calcium alginate fibers through particles, so that the micro-cross-linked gel particles are fixed on the surface of the non-woven material, and the calcium alginate fibers are entangled with each other through the entanglement between the molecular chains. In the ion exchange, the micro-cross-linked gel particles can act as a fixed point to avoid the molecular weight of sodium alginate from breaking in the later stage. In addition, compared with the hydroxyl group in sodium alginate, the ester group and the amino group in chitosan are more polar and have stronger interaction with water molecules. They can attract more water molecules through intermolecular forces other than hydrogen bonds, thereby improving the water absorption capacity and the release capacity of water molecules. When preparing nano-microspheres, firstly, vinyl trimethoxy silane and 3-aminopropyl trimethoxy silane are used to treat the surface of fumed silica, and vinyl and amino groups are introduced on the surface of silica. Then, 4-vinyl pyridine and styrene react with vinyl to introduce pyridine and phenyl groups. The nitrogen atom in the pyridine group Both the phenyl group and the pyridine group have strong electron-withdrawing properties, so the electron cloud density near the nitrogen atom and the phenyl group in the pyridine group is very high. The calcium ions obtained after ion exchange carry a positive charge, and the calcium ions carry out nucleophilic attacks on the nitrogen atom and the phenyl group in the pyridine group. Therefore, the nitrogen atom and the phenyl group in the pyridine group can interact with the calcium ions to fix the calcium ions. After the calcium ions are fixed, the dispersibility becomes worse and coagulation occurs. Therefore, the nano-microspheres can control the cross-linking speed and cross-linking density of the calcium alginate fibers on the surface by removing the calcium ions on the surface of the non-woven material, and promote the internal ionic cross-linking and cross-linking, thereby improving the water absorption of the non-woven material for the prepared mask, avoiding the problem of inconsistent water absorption of the surface and the inside during water absorption, and a large size change rate after water absorption; (2) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention, wherein the prepared nonwoven material for a facial mask has high water absorption, and the weight change rate of the nonwoven material for a facial mask prepared by the present invention after being kept in water for 30 seconds is 2315-2489%, and the weight change rate after being kept in water for 30 minutes is 2776-2820%, and the calcium ion content on the surface of the nonwoven material for a facial mask is 13.4-13.8%, and the sodium ion content is 86.2-86.6%; (3) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention, wherein the prepared nonwoven material for a facial mask has a small dimensional change rate after absorbing water. The lateral dimensional change rate of the nonwoven material for a facial mask prepared by the present invention after absorbing water is 1.00-1.25%, and the longitudinal dimensional change rate is 1.25-1.50%; (4) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention, wherein the prepared nonwoven material for a facial mask does not produce an obvious sticky feeling during use and has high comfort; (5) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention, wherein the prepared nonwoven material for a facial mask will not affect the formula of the facial mask material body. The nonwoven material for a facial mask prepared by the present invention is immersed in water for 24 hours, and the weight change rate is 4.81-5.69%, and the conductivity of the water after immersion is 117-143 μS / cm; (6) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention, wherein the prepared nonwoven material for a facial mask does not cause the collapse of the fiber structure, and the thickness of the nonwoven material obtained after secondary impregnation is 0.47-0.72 mm; (7) The method for preparing a nonwoven material for a facial mask with high water absorption of the present invention, wherein the prepared nonwoven material for a facial mask releases water molecules easily after absorbing water, and has a good moisturizing effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a comparison chart of the non-woven material sample for facial mask prepared in Comparative Example 1 before and after immersion in deionized water. DETAILED DESCRIPTION

[0013] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0014] Example 1 A method for preparing a nonwoven material for a facial mask with high water absorption, specifically comprising: 1. Preparation of micro-cross-linked gel particles: (1) Preparing a mixed solution: adding 10 g of carboxymethyl chitosan and 1000 mL of deionized water into a reactor, controlling the temperature of the reactor to 40° C., controlling the stirring speed to 200 rpm, and stirring for 20 min to obtain a carboxymethyl chitosan aqueous solution; adding 14 g of sodium alginate and 1000 mL of deionized water into a reactor, controlling the temperature of the reactor to 40° C., controlling the stirring speed to 200 rpm, and stirring for 20 min to obtain a sodium alginate aqueous solution; mixing all of the above carboxymethyl chitosan aqueous solution, all of the above sodium alginate aqueous solution, and 0.7 mL of propylene glycol, and adding the mixture to an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to 25 kHz, and ultrasonically oscillating at room temperature for 30 min to obtain a mixed solution; The carboxymethyl chitosan has a carboxymethyl substitution degree of 0.9, a deacetylation degree of 90%, and a viscosity average molecular weight of 240 kDa; (2) Micro-crosslinking: add all the mixed solution obtained in the step (1) of preparing the mixed solution and 9000 mL of ethyl acetate into a reactor, control the stirring speed to 500 rpm, stir at room temperature for 3 h, remove the ethyl acetate by vacuum distillation, then add 0.2 g of calcium chloride and 0.5 g of citric acid into the reactor, control the temperature of the reactor to 90°C, control the stirring speed to 200 rpm, stir for 50 min, transfer to a dialysis bag with a molecular weight cutoff of 8000 Da, dialyze with deionized water for 40 h, replace the deionized water every 6 h, then transfer to a vacuum freeze dryer, control the temperature of the vacuum freeze dryer to -40°C, control the vacuum degree to 80 Pa, and vacuum freeze dry for 25 h to obtain micro-crosslinked gel particles; 2. Preparation of nanoparticles: (1) Silanization: 37 g of fumed silica, 400 mL of deionized water and 2400 mL of anhydrous ethanol were mixed and added to an ultrasonic oscillator, the frequency of the ultrasonic oscillator was controlled to 25 kHz, and ultrasonic oscillation was performed at room temperature for 30 min. The mixture was transferred to a reactor with a reflux device, the temperature in the reactor was controlled to 45°C, the stirring speed was controlled to 200 rpm, 5 g of vinyltrimethoxysilane and 30 g of 3-aminopropyltrimethoxysilane were added, and the mixture was stirred and refluxed for 10 min. Dilute hydrochloric acid was added dropwise to adjust the pH to 4, and the mixture was stirred and refluxed for 5 h. The mixture was transferred to a centrifuge, the centrifugal speed of the centrifuge was controlled to 11000 rpm, and the mixture was centrifuged for 18 min. The precipitate was washed with anhydrous ethanol and vacuum dried to obtain silanized fumed silica. The particle size of the fumed silica is 40 nm; The mass concentration of the dilute hydrochloric acid is 10%; (2) Grafting: Add all the silanized fumed silica obtained in the silanization step (1), 48 mL of 4-vinylpyridine, 45 mL of styrene, and 7000 mL of acetone into a reactor, continuously introduce nitrogen into the reactor at a rate of 900 mL / min, control the stirring speed of the reactor to 200 rpm, stir at room temperature for 25 min, control the temperature in the reactor to 60°C, add 3.2 g of azobisisobutyronitrile, stir for 5 h, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 11000 rpm, centrifuge for 18 min, wash the precipitate with acetone and dry it in vacuum to obtain nano-microspheres; 3. Preparing a first fiber web: opening, combing, and laying the calcium alginate fibers to obtain a first fiber web; The diameter of the calcium alginate fiber is 9 μm; The first fiber web has a grammage of 10 g / m 2 ; 4. Preparing a second fiber web: opening, combing, and laying the second fibers to obtain a second fiber web; The second fiber is a Tencel fiber; The diameter of the second fiber is 9 μm; The weight of the second fiber web is 20 g / m 2 ; 5. Spunlace: After superimposing the first fiber web obtained in the first fiber web prepared in step 3 and the second fiber web obtained in the second fiber web prepared in step 4, the spunlace is reinforced and then dried to obtain a spunlace nonwoven material; 6. Primary impregnation: Wind the spunlace nonwoven material on the warp beam, then add it into the warp beam cylinder, add the primary impregnation liquid into the warp beam cylinder, control the temperature in the warp beam cylinder to 40°C, and promote the primary impregnation liquid to circulate from inside to outside and from outside to inside through a circulation pump, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 4 cycles, and a total cycle time of 20 minutes. After the cycle is completed, the primary impregnation liquid in the warp beam cylinder is discharged to obtain the nonwoven material after the primary impregnation; The preparation method of the primary impregnation liquid is as follows: 11 g of micro-crosslinked gel particles and 2700 mL of deionized water are added into a reaction kettle, the stirring speed is controlled to 200 rpm, and the mixture is stirred for 15 minutes to obtain the primary impregnation liquid; The dosage ratio of the spunlace nonwoven material to the primary impregnation liquid is 100 g:2700 mL; 7. Secondary dipping: Keep the temperature in the warp cylinder in the first dipping in step 6 at 40°C, add the secondary dipping liquid to the warp cylinder, and promote the secondary dipping liquid to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 4 cycles, and a total cycle time of 20 minutes. After the cycle, the secondary dipping liquid in the warp cylinder is discharged, and a cleaning liquid is added. The primary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 2 cycles, and a total cycle time of 10 minutes. After the cycle, the primary cleaning liquid in the warp cylinder is discharged, and the secondary cleaning liquid is added. The secondary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump. The process of washing the 3rd cleaning liquid in the warp shaft cylinder is as follows: the 3rd cleaning liquid is added, and the 3rd cleaning liquid is promoted by a circulation pump to circulate from the inside to the outside and from the outside to the inside, and ... promoted, and the 3rd cleaning liquid is promoted by a circulation pump to circulate from the inside to the outside and from the outside to the inside, The preparation method of the secondary impregnation liquid is as follows: 55g of sodium salt and 2700mL of ethanol aqueous solution are added into a reaction kettle, the stirring speed is controlled to 200rpm, the mixture is stirred for 15min, and then the mixture is mixed with 13g of nano-microspheres and added into an ultrasonic oscillator, the frequency of the ultrasonic oscillator is controlled to 25kHz, and the mixture is ultrasonically oscillated for 30min at room temperature to obtain the secondary impregnation liquid; The sodium salt is sodium chloride; In the preparation of the secondary impregnation solution, the volume fraction of ethanol in the ethanol aqueous solution is 45%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the secondary dipping liquid in the second dipping in step 7 is 100 g:2700 mL; The primary cleaning solution is an ethanol aqueous solution with a volume fraction of 45%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the first cleaning solution in the second dipping in step 7 is 100 g:2700 mL; The secondary cleaning solution is an ethanol aqueous solution with a volume fraction of 55%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the secondary cleaning solution in the second dipping in step 7 is 100 g:2700 mL; The three cleaning solutions are 75% ethanol water solution by volume; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the tertiary cleaning solution in the second dipping in step 7 is 100 g:2700 mL; The four cleaning solutions are 95% ethanol aqueous solution by volume; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the fourth cleaning solution in the second dipping in step 7 is 100 g:2700 mL; 8. Post-processing: cutting, bagging, sterilizing and packaging the nonwoven material after the second impregnation to obtain the nonwoven material for facial mask.

[0015] This embodiment also provides a nonwoven material for facial mask with high water absorption prepared by the aforementioned preparation method.

[0016] Example 2 A method for preparing a nonwoven material for a facial mask with high water absorption, specifically comprising: 1. Preparation of micro-cross-linked gel particles: (1) Preparing a mixed solution: adding 12 g of carboxymethyl chitosan and 1050 mL of deionized water into a reactor, controlling the temperature of the reactor to 45° C., controlling the stirring speed to 300 rpm, and stirring for 25 min to obtain a carboxymethyl chitosan aqueous solution; adding 15 g of sodium alginate and 1050 mL of deionized water into a reactor, controlling the temperature of the reactor to 45° C., controlling the stirring speed to 300 rpm, and stirring for 25 min to obtain a sodium alginate aqueous solution; mixing all of the above carboxymethyl chitosan aqueous solution, all of the above sodium alginate aqueous solution, and 0.7 mL of propylene glycol, and adding the mixture to an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to 25 kHz, and ultrasonically oscillating at room temperature for 35 min to obtain a mixed solution; The carboxymethyl chitosan has a carboxymethyl substitution degree of 0.9, a deacetylation degree of 90%, and a viscosity average molecular weight of 240 kDa; (2) Micro-crosslinking: add all the mixed solution obtained in the step (1) of preparing the mixed solution and 9100 mL of ethyl acetate into a reactor, control the stirring speed to 550 rpm, stir at room temperature for 3 h, remove the ethyl acetate by vacuum distillation, then add 0.25 g of calcium chloride and 0.55 g of citric acid into the reactor, control the temperature of the reactor to 92°C, control the stirring speed to 300 rpm, stir for 55 min, transfer to a dialysis bag with a molecular weight cutoff of 8000 Da, dialyze with deionized water for 45 h, replace the deionized water every 7 h, then transfer to a vacuum freeze dryer, control the temperature of the vacuum freeze dryer to -35°C, control the vacuum degree to 90 Pa, and vacuum freeze dry for 27 h to obtain micro-crosslinked gel particles; 2. Preparation of nanoparticles: (1) Silanization: 39 g of fumed silica, 450 mL of deionized water and 2500 mL of anhydrous ethanol were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 25 kHz. The mixture was ultrasonically oscillated at room temperature for 35 min. The mixture was transferred to a reactor with a reflux device. The temperature in the reactor was controlled to 50°C and the stirring speed was controlled to 300 rpm. 5.2 g of vinyl trimethoxy silane and 31 g of 3-aminopropyl trimethoxy silane were added. The mixture was stirred and refluxed for 15 min. Dilute hydrochloric acid was added dropwise to adjust the pH to 4.2. The mixture was stirred and refluxed for 5.5 h. The mixture was transferred to a centrifuge. The centrifugal speed of the centrifuge was controlled to 11000 rpm. The mixture was centrifuged for 19 min. The precipitate was washed with anhydrous ethanol and vacuum dried to obtain silanized fumed silica. The particle size of the fumed silica is 40 nm; The mass concentration of the dilute hydrochloric acid is 10%; (2) Grafting: Add all the silanized fumed silica obtained in the silanization step (1), 49 mL of 4-vinylpyridine, 48 mL of styrene, and 7200 mL of acetone into a reactor, continuously introduce nitrogen into the reactor at a rate of 950 mL / min, control the stirring speed of the reactor to 300 rpm, stir at room temperature for 30 min, control the temperature in the reactor to 65°C, add 3.4 g of azobisisobutyronitrile, stir for 5.5 h, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 11000 rpm, centrifuge for 19 min, wash the precipitate with acetone and vacuum dry to obtain nano-microspheres; 3. Preparing a first fiber web: opening, combing, and laying the calcium alginate fibers to obtain a first fiber web; The diameter of the calcium alginate fiber is 15 μm; The first fiber web has a grammage of 13 g / m 2 ; 4. Preparing a second fiber web: opening, combing, and laying the second fibers to obtain a second fiber web; The second fiber is viscose fiber; The diameter of the second fiber is 15 μm; The weight of the second fiber web is 30 g / m 2 ; 5. Spunlace: After superimposing the first fiber web obtained in the first fiber web prepared in step 3 and the second fiber web obtained in the second fiber web prepared in step 4, the spunlace is reinforced and then dried to obtain a spunlace nonwoven material; 6. Primary impregnation: Wind the spunlace nonwoven material on the warp beam, then add it into the warp beam cylinder, add the primary impregnation liquid into the warp beam cylinder, control the temperature in the warp beam cylinder to 45°C, and promote the primary impregnation liquid to circulate from inside to outside and from outside to inside through a circulation pump, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 4 cycles, and a total cycle time of 20 minutes. After the cycle is completed, the primary impregnation liquid in the warp beam cylinder is discharged to obtain the nonwoven material after the primary impregnation; The preparation method of the primary impregnation liquid is as follows: 11.5 g of micro-crosslinked gel particles and 2800 mL of deionized water are added into a reaction kettle, the stirring speed is controlled to 250 rpm, and the stirring is performed for 18 minutes to obtain the primary impregnation liquid; The usage ratio of spunlace nonwoven material to primary impregnation liquid is 110 g:2900 mL; 7. Secondary dipping: Keep the temperature in the warp cylinder in the first dipping of step 6 at 45°C, add the secondary dipping liquid to the warp cylinder, and promote the secondary dipping liquid to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 5 cycles, and a total cycle time of 22 minutes. After the cycle, the secondary dipping liquid in the warp cylinder is discharged, and a cleaning liquid is added. The primary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 2 cycles, and a total cycle time of 10 minutes. After the cycle, the primary cleaning liquid in the warp cylinder is discharged, and the secondary cleaning liquid is added. The secondary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump. The process of washing the 3rd cleaning liquid in the warp shaft cylinder is as follows: the 3rd cleaning liquid is added, and the 3rd cleaning liquid is promoted by a circulation pump to circulate from the inside to the outside and from the outside to the inside, and ... promoted, and the 3rd cleaning liquid is promoted by a circulation pump to circulate from the inside to the outside and from the outside to the inside, The preparation method of the secondary impregnation liquid is as follows: 58g of sodium salt and 2900mL of ethanol aqueous solution are added into a reaction kettle, the stirring speed is controlled to 250rpm, the mixture is stirred for 18min, and then the mixture is mixed with 14g of nano-microspheres and added into an ultrasonic oscillator, the frequency of the ultrasonic oscillator is controlled to 25kHz, and the mixture is ultrasonically oscillated for 35min at room temperature to obtain a secondary impregnation liquid; The sodium salt is sodium bicarbonate; In the preparation of the secondary impregnation solution, the volume fraction of ethanol in the ethanol aqueous solution is 65%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the secondary dipping liquid in the second dipping in step 7 is 110 g:2900 mL; The primary cleaning solution is an ethanol aqueous solution with a volume fraction of 45%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the first cleaning solution in the second dipping in step 7 is 110 g:2900 mL; The secondary cleaning solution is an ethanol aqueous solution with a volume fraction of 55%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the secondary cleaning solution in the second dipping in step 7 is 110 g:2900 mL; The three cleaning solutions are 75% ethanol water solution by volume; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the tertiary cleaning solution in the second dipping in step 7 is 110 g:2900 mL; The four cleaning solutions are 95% ethanol aqueous solution by volume; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the fourth cleaning solution in the second dipping in step 7 is 110 g:2900 mL; 8. Post-processing: cutting, bagging, sterilizing and packaging the nonwoven material after the second impregnation to obtain the nonwoven material for facial mask.

[0017] This embodiment also provides a nonwoven material for facial mask with high water absorption prepared by the aforementioned preparation method.

[0018] Example 3 A method for preparing a nonwoven material for a facial mask with high water absorption, specifically comprising: 1. Preparation of micro-cross-linked gel particles: (1) Preparing a mixed solution: adding 15 g of carboxymethyl chitosan and 1100 mL of deionized water into a reactor, controlling the temperature of the reactor to 50° C., controlling the stirring speed to 400 rpm, and stirring for 30 min to obtain a carboxymethyl chitosan aqueous solution; adding 16 g of sodium alginate and 1100 mL of deionized water into a reactor, controlling the temperature of the reactor to 50° C., controlling the stirring speed to 400 rpm, and stirring for 30 min to obtain a sodium alginate aqueous solution; mixing all of the above carboxymethyl chitosan aqueous solution, all of the above sodium alginate aqueous solution, and 0.8 mL of propylene glycol, and adding the mixture to an ultrasonic oscillator, controlling the frequency of the ultrasonic oscillator to 30 kHz, and ultrasonically oscillating at room temperature for 40 min to obtain a mixed solution; The carboxymethyl chitosan has a carboxymethyl substitution degree of 0.9, a deacetylation degree of 90%, and a viscosity average molecular weight of 240 kDa; (2) Micro-crosslinking: add all the mixed solution obtained in the step of preparing the mixed solution in step (1) and 9200 mL of ethyl acetate into a reactor, control the stirring speed to 600 rpm, stir at room temperature for 3.5 hours, remove the ethyl acetate by vacuum distillation, then add 0.3 g of calcium chloride and 0.6 g of citric acid into the reactor, control the temperature of the reactor to 95°C, control the stirring speed to 400 rpm, stir for 60 minutes, transfer to a dialysis bag with a molecular weight cutoff of 8000 Da, dialyze with deionized water for 50 hours, replace the deionized water every 8 hours, then transfer to a vacuum freeze dryer, control the temperature of the vacuum freeze dryer to -30°C, control the vacuum degree to 100 Pa, and vacuum freeze dry for 30 hours to obtain micro-crosslinked gel particles; 2. Preparation of nanoparticles: (1) Silanization: 40 g of fumed silica, 500 mL of deionized water and 2600 mL of anhydrous ethanol were mixed and added to an ultrasonic oscillator. The frequency of the ultrasonic oscillator was controlled to 30 kHz. The mixture was ultrasonically oscillated at room temperature for 40 min. The mixture was transferred to a reactor with a reflux device. The temperature in the reactor was controlled to 55 ° C. The stirring speed was controlled to 400 rpm. 5.5 g of vinyl trimethoxysilane and 32 g of 3-aminopropyl trimethoxysilane were added. The mixture was stirred and refluxed for 20 min. Dilute hydrochloric acid was added dropwise to adjust the pH to 4.5. The mixture was stirred and refluxed for 6 h. The mixture was transferred to a centrifuge. The centrifugal speed of the centrifuge was controlled to 12000 rpm. The mixture was centrifuged for 20 min. The precipitate was washed with anhydrous ethanol and vacuum dried to obtain silanized fumed silica. The particle size of the fumed silica is 40 nm; The mass concentration of the dilute hydrochloric acid is 10%; (2) Grafting: Add all the silanized fumed silica obtained in the silanization step (1), 50 mL of 4-vinylpyridine, 50 mL of styrene, and 7500 mL of acetone into a reactor, continuously introduce nitrogen into the reactor at a rate of 1000 mL / min, control the stirring speed of the reactor to 400 rpm, stir at room temperature for 35 min, control the temperature in the reactor to 70°C, add 3.5 g of azobisisobutyronitrile, stir for 6 h, transfer to a centrifuge, control the centrifugal speed of the centrifuge to 12000 rpm, centrifuge for 20 min, wash the precipitate with acetone and vacuum dry to obtain nanospheres; 3. Preparing a first fiber web: opening, combing, and laying the calcium alginate fibers to obtain a first fiber web; The diameter of the calcium alginate fiber is 20 μm; The first fiber web has a grammage of 15 g / m 2 ; 4. Preparing a second fiber web: opening, combing, and laying the second fibers to obtain a second fiber web; The second fiber is cotton fiber; The diameter of the second fiber is 20 μm; The weight of the second fiber web is 40 g / m 2 ; 5. Spunlace: After superimposing the first fiber web obtained in the first fiber web prepared in step 3 and the second fiber web obtained in the second fiber web prepared in step 4, the spunlace is reinforced and then dried to obtain a spunlace nonwoven material; 6. Primary impregnation: Wind the spunlace nonwoven material on the warp beam, then add it into the warp beam cylinder, add the primary impregnation liquid into the warp beam cylinder, control the temperature in the warp beam cylinder to 50°C, and promote the primary impregnation liquid to circulate from inside to outside and from outside to inside through a circulation pump, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 5 cycles, the total cycle time is 25 minutes, and after the cycle is completed, the primary impregnation liquid in the warp beam cylinder is discharged to obtain the nonwoven material after the primary impregnation; The preparation method of the primary impregnation liquid is as follows: 12 g of micro-crosslinked gel particles and 3000 mL of deionized water are added into a reaction kettle, the stirring speed is controlled to 300 rpm, and the stirring is performed for 20 minutes to obtain the primary impregnation liquid; The usage ratio of spunlace nonwoven material to primary impregnation liquid is 120 g:3000 mL; 7. Secondary dipping: Keep the temperature in the warp cylinder in the first dipping in step 6 at 50°C, add the secondary dipping liquid to the warp cylinder, and promote the secondary dipping liquid to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 5 cycles, and a total cycle time of 25 minutes. After the cycle, the secondary dipping liquid in the warp cylinder is discharged, and a cleaning liquid is added. The primary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump, with one cycle from the inside to the outside and then from the outside to the inside as one cycle, a total of 3 cycles, and a total cycle time of 15 minutes. After the cycle, the primary cleaning liquid in the warp cylinder is discharged, and the secondary cleaning liquid is added. The secondary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump. Cycle, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 3 cycles, a total cycle time of 15 minutes, after the cycle is completed, the secondary cleaning liquid in the warp axis cylinder is discharged, and the tertiary cleaning liquid is added, and the tertiary cleaning liquid is promoted by a circulation pump to circulate from inside to outside and from outside to inside, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 3 cycles, a total cycle time of 15 minutes, after the cycle is completed, the tertiary cleaning liquid in the warp axis cylinder is discharged, and the quaternary cleaning liquid is added, and the quaternary cleaning liquid is promoted by a circulation pump to circulate from inside to outside and from outside to inside, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 3 cycles, a total cycle time of 15 minutes, and after the cycle is completed, it is rolled and dried to obtain a non-woven material after secondary impregnation; The preparation method of the secondary impregnation liquid is as follows: 60g of sodium salt and 3000mL of ethanol aqueous solution are added into a reaction kettle, the stirring speed is controlled to 300rpm, and the mixture is stirred for 20min, and then the mixture is mixed with 15g of nano-microspheres and added into an ultrasonic oscillator, the frequency of the ultrasonic oscillator is controlled to 30kHz, and the mixture is ultrasonically oscillated at room temperature for 40min to obtain a secondary impregnation liquid; The sodium salt is sodium citrate; In the preparation of the secondary impregnation solution, the volume fraction of ethanol in the ethanol aqueous solution is 85%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the secondary dipping liquid in the second dipping in step 7 is 120 g:3000 mL; The primary cleaning solution is an ethanol aqueous solution with a volume fraction of 45%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the first cleaning solution in the second dipping in step 7 is 120 g:3000 mL; The secondary cleaning solution is an ethanol aqueous solution with a volume fraction of 55%; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the secondary cleaning solution in the second dipping in step 7 is 120 g:3000 mL; The three cleaning solutions are 75% ethanol water solution by volume; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the tertiary cleaning solution in the second dipping in step 7 is 120 g:3000 mL; The four cleaning solutions are 95% ethanol aqueous solution by volume; The amount ratio of the spunlace nonwoven material in the first dipping in step 6 to the fourth cleaning solution in the second dipping in step 7 is 120 g:3000 mL; 8. Post-processing: cutting, bagging, sterilizing and packaging the nonwoven material after the second impregnation to obtain the nonwoven material for facial mask.

[0019] This embodiment also provides a nonwoven material for facial mask with high water absorption prepared by the aforementioned preparation method.

[0020] Comparative Example 1 On the basis of Example 1, the first step of preparing micro-crosslinked gel particles is omitted, and the first impregnation in the sixth step is omitted, that is, the spunlace nonwoven material obtained by spunlace in the fifth step is wound on the warp axis, and then added to the warp axis cylinder, and then the secondary impregnation liquid is directly added to the warp axis cylinder.

[0021] The rest of the operations are the same as those in Example 1.

[0022] Comparative Example 2 On the basis of Example 1, the second step of preparing nano-microspheres is omitted, and in the second impregnation step 7, the addition of nano-microspheres is omitted in the preparation of the second impregnation solution, that is, the preparation method of the second impregnation solution is changed to: 55 g of sodium salt and 2700 mL of ethanol aqueous solution were added into the reactor, the stirring speed was controlled to 200 rpm, and the mixture was stirred for 15 min to obtain a secondary impregnation solution.

[0023] The rest of the operations are the same as those in Example 2.

[0024] Performance Test 1 The water absorption of the nonwoven materials for facial masks prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the test method was as follows: After drying the nonwoven materials for facial masks prepared in Examples 1-3 and Comparative Examples 1-2 to constant weight, cut out samples of the nonwoven materials for facial masks with a size of 20 cm×20 cm, weigh them and record them as m1, and completely immerse the nonwoven materials for facial masks in 1 L of deionized water for a certain period of time, take them out, hold one corner of the sample with tweezers, hang them for 30 seconds, weigh them and record them as m2, and calculate the weight change rate. The calculation formula of the weight change rate is as follows: Weight change rate = (m2-m1) / m1×100%; Take samples and test them three times continuously, and calculate the average weight change rate; When the holding time is 30s and 30min respectively, the calculated average weight change rate results are as follows:

[0025] It can be seen from the results of this test example that the use of micro-crosslinked gel particles and nano-microspheres can improve the water absorption of the nonwoven material for facial mask.

[0026] Performance Test 2 The calcium ion and sodium ion content on the surface of the nonwoven material for facial mask prepared in Examples 1-3 and Comparative Examples 1-2 were tested by EDS analysis, and the test results are as follows:

[0027] It can be seen from the results of this test example that the use of nano-microspheres can reduce the calcium ion content on the surface of the nonwoven material for facial mask.

[0028] Performance Test 3 The thickness of the spunlace nonwoven material obtained after the spunlace in step 5 and the secondary impregnation nonwoven material obtained after the secondary impregnation in step 7 in Examples 1-3 and Comparative Examples 1-2 was tested, and the test results are as follows:

[0029] It can be seen from the results of this test example that the use of micro-crosslinked gel particles and nano-microspheres can increase the thickness of the secondary impregnated nonwoven material obtained after secondary impregnation.

[0030] Performance Test 4 After drying the nonwoven materials for facial masks prepared in Examples 1-3 and Comparative Examples 1-2 to constant weight, the nonwoven material samples for facial masks with a size of 20 cm×20 cm were cut out respectively, and sufficient water was sprayed on the surface of the samples to wet them, and the sizes were tested, and the transverse size change rate and the longitudinal size change rate were calculated. The calculation results are as follows:

[0031] It can be seen from the results of this test example that the use of micro-cross-linked gel particles and nano-microspheres can reduce the dimensional change rate of the nonwoven material for facial mask after absorbing water.

[0032] Performance Test 5 After the nonwoven materials for facial masks prepared in Examples 1-3 and Comparative Examples 1-2 were dried to constant weight, samples were taken and weighed, recorded as m1g, and the nonwoven material samples for facial masks were completely immersed in 200 mL of deionized water for 24 h, taken out, dried to constant weight and weighed, recorded as m2g, and the weight change rate was calculated. The calculation formula of the weight change rate is as follows: Weight change rate = (m2-m1) / m1×100%; The conductivity of the deionized water after immersion was tested, and the results of m1, m2, weight change rate, and conductivity are as follows:

[0033] It can be seen from the results of this test example that the use of micro-cross-linked gel particles and nano-microspheres can reduce the weight change rate of the nonwoven material for facial mask after long-term immersion and the conductivity of deionized water after immersion.

[0034] The nonwoven material sample of the mask prepared in Comparative Example 1 was photographed and compared before and after being immersed in deionized water. The comparison diagram obtained is shown in FIG. Figure 1 , where the beaker on the left contains deionized water before immersion, and the beaker on the back contains deionized water after immersion. Figure 1 It can be seen that the deionized water before immersion is clear and transparent, and the deionized water after immersion is whitish, which further illustrates that sodium alginate is dissolved in the nonwoven material sample for facial mask prepared in Comparative Example 1 during immersion.

[0035] Performance Test 6 50 female volunteers aged 18-35 were selected and randomly divided into 5 groups, namely Groups 1-5. The nonwoven materials for facial masks prepared in Examples 1-3 and Comparative Examples 1-2 were completely immersed in deionized water, left to stand for 1 minute, and then taken out and applied to the face of each female volunteer in Groups 1-5, respectively. After 20 minutes of static application, the masks were removed, and each female volunteer was asked to score the comfort, and the average score was calculated. The scoring standard and calculation results are as follows: 4-5 points: non-sticky and highly comfortable; 3-4 points: slightly sticky, relatively comfortable; 2-3 points: relatively sticky, average comfort; 1-2 points: Very sticky and poor comfort; 0-1 points: very sticky, poor comfort;

[0036] It can be seen from the results of this test example that the use of micro-cross-linked gel particles and nano-microspheres can improve the comfort of the nonwoven material for facial mask during use.

[0037] Performance Test 7 50 female volunteers aged 18-35 were selected and randomly divided into 5 groups, namely Groups 1-5. The skin moisture content of each female volunteer was tested respectively as the initial skin moisture content, and the average initial skin moisture content of each group was calculated. The nonwoven materials for the facial masks prepared in Examples 1-3 and Comparative Examples 1-2 were completely immersed in deionized water, taken out after standing for 1 minute, and applied to the faces of the female volunteers in Groups 1-5 respectively. After 20 minutes of static application, the masks were removed, and the skin moisture content of each female volunteer was tested respectively as the skin moisture content after wet application, and the average skin moisture content after wet application of each group was calculated. The difference between the average skin moisture content after wet application of each group and the average initial skin moisture content was calculated, and the calculation results are as follows:

[0038] It can be seen from the results of this test example that the use of micro-cross-linked gel particles and nano-microspheres can improve the moisturizing effect of the nonwoven material for facial mask.

[0039] Unless otherwise specified, all percentages used in the present invention are by mass.

[0040] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nonwoven material for a facial mask with high water absorption, characterized in that: The method comprises the following steps: preparing micro-crosslinked gel particles, preparing nano-microspheres, preparing a first fiber web, preparing a second fiber web, hydroentangling, primary dipping, secondary dipping, and post-treatment; The method for preparing micro-crosslinked gel particles comprises the following steps: preparing a mixed solution, micro-crosslinking; The mixed solution is prepared by mixing carboxymethyl chitosan and the first portion of deionized water, and stirring at 40-50° C. to obtain a carboxymethyl chitosan aqueous solution; mixing sodium alginate and the second portion of deionized water, and stirring at 40-50° C. to obtain a sodium alginate aqueous solution; and uniformly mixing the carboxymethyl chitosan aqueous solution, the sodium alginate aqueous solution, and glycerol to obtain a mixed solution; The micro-crosslinking comprises mixing the mixed solution and ethyl acetate, stirring at room temperature, removing the ethyl acetate by reduced pressure distillation, mixing with calcium chloride and citric acid, stirring at 90-95° C., transferring to a dialysis bag, dialyzing with deionized water, and then vacuum freeze-drying to obtain micro-crosslinked gel particles; The preparation of nano-microspheres is composed of the following steps: silanization and grafting; The silanization comprises mixing fumed silica, deionized water and anhydrous ethanol uniformly, mixing with vinyl trimethoxysilane and 3-aminopropyl trimethoxysilane, stirring and refluxing at 45-55° C., adjusting the pH to 4-4.5, stirring and refluxing, centrifuging, washing the precipitate and vacuum drying to obtain silanized fumed silica; The grafting comprises mixing silanized fumed silica, 4-vinylpyridine, styrene and acetone, stirring at room temperature under the protection of nitrogen, adding azobisisobutyronitrile, stirring at 60-70° C., transferring and centrifuging, washing the precipitate and vacuum drying to obtain nano-microspheres; The primary impregnation comprises winding the spunlace nonwoven material on a warp beam, and then adding the spunlace nonwoven material into a warp beam cylinder, adding a primary impregnation liquid into the warp beam cylinder, controlling the temperature in the warp beam cylinder to be 40-50° C., and promoting the primary impregnation liquid to circulate from inside to outside and from outside to inside by a circulation pump, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 4-5 cycles, and a total cycle time of 20-25 minutes. After the cycle is completed, the primary impregnation liquid in the warp beam cylinder is discharged to obtain a nonwoven material after the primary impregnation; The preparation method of the primary impregnation liquid is as follows: adding micro-crosslinked gel particles and deionized water into a reaction kettle, controlling the stirring speed to 200-300 rpm, stirring for 15-20 minutes, and obtaining the primary impregnation liquid; The secondary impregnation includes maintaining the temperature in the warp axis cylinder during the primary impregnation at 40-50° C., adding the secondary impregnation liquid into the warp axis cylinder, and promoting the secondary impregnation liquid to circulate from inside to outside and from outside to inside through a circulation pump, with one cycle from inside to outside and then from outside to inside as one cycle, a total of 4-5 cycles, and a total cycle time of 20-25 minutes. After the cycle is completed, the secondary impregnation liquid in the warp axis cylinder is discharged, and the non-woven material after the secondary impregnation is washed, rolled and dried to obtain the non-woven material after the secondary impregnation; The preparation method of the secondary impregnation liquid is as follows: sodium salt and ethanol aqueous solution are added into a reaction kettle, the stirring speed is controlled to 200-300 rpm, the stirring is performed for 15-20 minutes, and then the mixture is mixed with nano-microspheres and added into an ultrasonic oscillator, the frequency of the ultrasonic oscillator is controlled to 25-30 kHz, and the mixture is ultrasonically oscillated for 30-40 minutes at room temperature to obtain the secondary impregnation liquid.

2. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 1, characterized in that: In the prepared mixed solution, the dosage ratio of carboxymethyl chitosan, the first portion of deionized water, sodium alginate, the second portion of deionized water, and glycerol is 10-15 g: 1000-1100 mL: 14-16 g: 1000-1100 mL: 0.7-0.8 mL; The carboxymethyl chitosan has a carboxymethyl substitution degree of 0.9, a deacetylation degree of 90%, and a viscosity average molecular weight of 240 kDa; The ratio of carboxymethyl chitosan in the prepared mixed solution to ethyl acetate, calcium chloride and citric acid in the micro-crosslinking is 10-15 g: 9000-9200 mL: 0.2-0.3 g: 0.5-0.6 g; In the micro-crosslinking, the molecular weight cut-off of the dialysis bag is 8000Da; The dialysis time is 40-50 hours, and the deionized water is replaced every 6-8 hours during dialysis; The vacuum freeze drying process is carried out at a temperature of -40°C to -30°C, a vacuum degree of 80-100 Pa, and a time of 25-30 hours.

3. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 1, characterized in that: In the silanization, the usage ratio of fumed silica, deionized water, anhydrous ethanol, vinyl trimethoxysilane and 3-aminopropyl trimethoxysilane is 37-40 g: 400-500 mL: 2400-2600 mL: 5-5.5 g: 30-32 g; The particle size of the fumed silica is 40 nm; The usage ratio of the fumed silica in the silanization to the 4-vinylpyridine, styrene, acetone and azobisisobutyronitrile in the grafting is 37-40g:48-50mL:45-50mL:7000-7500mL:3.2-3.5g.

4. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 1, characterized in that: The first fiber web is prepared by opening, combing and laying the calcium alginate fibers to obtain the first fiber web; In the preparation of the first fiber web, the diameter of the calcium alginate fiber is 9-20 μm; The first fiber web has a grammage of 10-15 g / m 2 ; The second fiber web is prepared by opening, combing and laying the second fibers to obtain the second fiber web; In the preparation of the second fiber web, the second fiber is one of tencel fiber, viscose fiber and cotton fiber; The diameter of the second fiber is 9-20 μm; The second fiber web has a grammage of 20-40 g / m 2 ; The hydroentanglement is performed by superimposing the first fiber web and the second fiber web, and then performing hydroentanglement reinforcement and drying to obtain a hydroentangled nonwoven material.

5. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 1, characterized in that: In the preparation of the primary impregnation solution, the ratio of micro-crosslinked gel particles to deionized water is 11-12 g: 2700-3000 mL; In the primary impregnation, the amount ratio of the spunlace nonwoven material to the primary impregnation liquid is 100-120 g: 2700-3000 mL; In the preparation of the secondary impregnation solution, the dosage ratio of sodium salt, ethanol aqueous solution and nano-microspheres is 55-60 g: 2700-3000 mL: 13-15 g; The sodium salt is one of sodium chloride, sodium carbonate, sodium bicarbonate, disodium ethylenediaminetetraacetate, and sodium citrate; In the preparation of the secondary impregnation solution, the volume fraction of ethanol in the ethanol aqueous solution is 45-85%; The amount ratio of the spunlace nonwoven material in the first dipping to the secondary dipping liquid in the second dipping is 100-120 g: 2700-3000 mL.

6. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 1, characterized in that: The cleaning comprises adding a cleaning liquid into the warp axis cylinder, promoting the cleaning liquid to circulate from the inside to the outside and from the outside to the inside through a circulation pump, taking from the inside to the outside once and then from the outside to the inside once as one cycle, circulating 2-3 times in total, and the total cycle time is 10-15 minutes. After the cycle is completed, the cleaning liquid in the warp axis cylinder is discharged, and a secondary cleaning liquid is added, and the secondary cleaning liquid is promoted to circulate from the inside to the outside and from the outside to the inside through a circulation pump, taking from the inside to the outside once and then from the outside to the inside once as one cycle, circulating 2-3 times in total, and the total cycle time is 10-15 minutes. The cycle is completed. Finally, the secondary cleaning liquid in the warp axis cylinder is discharged, and the tertiary cleaning liquid is added. The circulation pump is used to promote the tertiary cleaning liquid to circulate from the inside to the outside and from the outside to the inside. One cycle is from the inside to the outside and then from the outside to the inside. A total of 2-3 cycles are performed, and the total cycle time is 10-15 minutes. After the cycle, the tertiary cleaning liquid in the warp axis cylinder is discharged, and the fourth cleaning liquid is added. The circulation pump is used to promote the fourth cleaning liquid to circulate from the inside to the outside and from the outside to the inside. A cycle is taken from the inside to the outside and then from the outside to the inside as one cycle. A total of 2-3 cycles are performed, and the total cycle time is 10-15 minutes.

7. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 6, characterized in that: In the cleaning, the primary cleaning liquid is an ethanol aqueous solution with a volume fraction of 45%; The amount ratio of the spunlace nonwoven material in the first immersion to the first cleaning liquid in the second immersion is 100-120 g: 2700-3000 mL; The secondary cleaning solution is an ethanol aqueous solution with a volume fraction of 55%; The amount ratio of the spunlace nonwoven material in the first immersion to the secondary cleaning liquid in the second immersion is 100-120 g: 2700-3000 mL; The three cleaning solutions are 75% ethanol water solution by volume; The amount ratio of the spunlace nonwoven material in the first immersion to the tertiary cleaning solution in the second immersion is 100-120 g: 2700-3000 mL; The four cleaning solutions are 95% ethanol aqueous solution by volume; The usage ratio of the spunlace nonwoven material in the first immersion to the fourth cleaning liquid in the second immersion is 100-120 g: 2700-3000 mL.

8. The method for preparing a nonwoven material for a facial mask having high water absorption according to claim 1, characterized in that: The post-treatment is to cut, bag, sterilize and package the nonwoven material after the second impregnation to obtain the nonwoven material for facial mask.

9. A nonwoven material for facial mask with high water absorption prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Carboxymethyl chitosan / sodium alginate nano hydrogel as well as preparation method and application

    CN110623918A

  • Composite magnetic nanoparticle and preparation method and application thereof

    CN113368834A

  • Drug-loadable sodium alginate microspheres and preparation method thereof

    CN118892458A

  • Curable composition, sealing material and adhesive

    JP2004292620A

  • Low staining aqueous coating composition and object coated with the same

    JP2008239779A